Numerical analysis and optimization for natural ventilation of Jurong Industrial Estate via CFD modelling and simulation - Abhilash Agarwal (Nanyang Technological University, 2021)
With a consistent rise in global temperature, we increasingly invest our resources in identifying ways to keep our surroundings cooler. Even though the most used solutions are found in durable consumer products like refrigerators, and air conditioners, these electronics, in turn, are also adding to the environmental burden of increasing temperature. While we heavily rely on air conditioning in residential and corporate spaces, many premises like industries and manufacturing plants are deemed to provide unfavorable working conditions due to a lack of control on indoor temperature. Additionally, humanity’s constant need for advancement comes at the cost of our environment, where developing and developed economies are successively contributing to the rising levels of greenhouse gases, industrial and urban pollution. Hence, it is imperative to identify such a solution that can naturally decrease the temperature of an area without any additional costs. One such solution is to leverage on ventilation techniques to optimize the layout of premises and naturally bring down the temperature, which in turn can also lessen our reliance on electronics. This research highlights the importance of layout, specifically in an industrial environment. It focuses on effective planning and design guidelines to improve the layout of Jurong Industrial Estate in Singapore to obtain higher energy efficiency i.e. lower temperature value. First model (Model S1-1) is an exact replica of Jurong Industrial Estate. Second model (Model S1-2) is an edited version of Model S1-1 where buildings are oriented along east west line without shuffling. Third model (Model S1-3) is an edited version of Model S1-1 where buildings are oriented along east west line with shuffling. Fourth model (Model S1-4) is the edited version of Model S1-1 where buildings were oriented along the north-south line. By performing different orientation Computational Fluid Dynamics (CFD) simulations are conducted using ANSYS Fluent. Through this research, it is concluded that the temperature of the system can be reduced by changing the layout of the building in the planning stages. We proposed that Model S1-3 has the lowest energy in its vicinity among all the other models that were created. The temperature drop is observed from Model S1-1 to Model S1-3 from 306.4oK to 305.4oK with a drop in velocity of about 15% and a pressure drop of about 35%. There is consistent evidence showing that Model S1-3 is better in every way than Model S1-1 whether it be change in temperature, pressure and velocity.